Effects of acid inhibition on somatostatin-producing cells in the rat gastric fundus - (:unkn) unknown (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2001)
Somatostatin plays a role in the regulation of gastric acid secretion. Omeprazole, a potent inhibitor of gastric acid secretion, has been reported to cause either a significant decrease or increase in the formation of gastric somatostatin-producing cells. Therefore, we determined in the present study distribution patterns of somatostatin mRNA and protein in fundus mucosa of rats after long-term inhibition of gastric acid secretion. Female Sprague-Dawley rats were given 0, 20 and 100 mg/kg/day omeprazole, respectively, as gastric instillations during 2 months. Serum gastrin levels were significantly higher in the third group than in the other groups. The omeprazole-treated groups also showed an increase in the number of somatostatin-containing cells in fundus mucosa. Moreover, the intensity of somatostatin-positivity was higher in the treated groups than in the control group. We also observed an increase in the number of cells containing somatostatin mRNA. in fundus mucosa of omeprazole-treated rats. These results suggest that long-term inhibition of acid secretion does not inhibit but stimulate somatostatin production in mucosa of rat gastric fundus.
Keywords: somatostatin; omeprazole; gastric fundus; TERM OMEPRAZOLE TREATMENT; ENDOCRINE-CELLS; GASTROINTESTINAL SOMATOSTATIN; INDUCED ACHLORHYDRIA; ANTRECTOMIZED RATS; GENE-EXPRESSION; ANTRAL GASTRIN; PLASMA GASTRIN; SECRETION; STOMACH